Kesalahan Konseptual dalam Penyelesaian Soal Fungsi Kuadrat: Perspektif Mahasiswa Pendidikan Ekonomi - Fahrudin, Ahmad; Robbani, Hamzah (NUCLEUS, 2024)
This study aims to identify errors made by students in solving problems about Quadratic Functions in the context of the application of economic mathematics. The method used in this research is qualitative research with a descriptive approach. The research subjects consisted of students of Economic Education Study Programme of Ndraprasta PGRI University. Data collection techniques are carried out systematically and in accordance with predetermined procedures. This systematic method involves measurement techniques to evaluate students' abilities in Quadratic Function Application material in Economics through the administration of a questionnaire containing 5 description questions. The results showed that students experienced errors in working on Quadratic Function material in the application of economic mathematics, where 39% of students did not understand the concept. In addition, 31.3% per cent of students did not understand the correct steps to solve the problem, and there were also errors in the process of solving the problem. Students' accuracy in solving problems is also relatively low, and 29.3% of students who are able to solve perfectly. Thus, the level of error in this material is still very high among students.